Pharmacokinetic Evaluation by Modeling and Simulation Analysis of a Donepezil Patch Formulation in Healthy Male Volunteers - Yoon SK; Bae KS; Hong DH; Kim SS; Choi YK; Lim HS (Dove Medical Press, 2020)
Seok Kyu Yoon,1 Kyun-Seop Bae,1 Dong Hyun Hong,2 Seong Su Kim,2 Young Kweon Choi,2 Hyeong-Seok Lim1 1Department of Clinical Pharmacology and Therapeutics, College of Medicine, University of Ulsan, Asan Medical Center, Seoul, Republic of Korea; 2Department of Pharmaceutical Research, iCure Pharmaceutical Incorporated, Seoul, Republic of KoreaCorrespondence: Hyeong-Seok LimDepartment of Clinical Pharmacology and Therapeutics, Asan Medical Center, University of Ulsan College of Medicine, Songpa-Gu, Seoul Tel +82-2-3010-4623Fax +82-2-3010-4622Email mdlhs@amc.seoul.krIntroduction: This study characterized the pharmacokinetics (PKs) of a donepezil patch formulation currently under development, using mixed effect modeling analysis, and explored optimal patch dosing regimens in comparison with the donepezil oral formulation.Methods: PK data used in this analysis were from 60 healthy Korean male subjects participating in two Phase I studies, where subjects received single or multiple doses of donepezil of 43.75, 87.5, and 175 mg via patches, and 12 of them received a single oral dose of 10 mg of donepezil, followed by a single dose of donepezil via a patch. Donepezil PKs were analyzed by nonlinear mixed effect modeling using NONMEM software.Results: A well-stirred model with two-compartment distribution and delayed absorption was chosen as the best model for the oral formulation. The PKs of donepezil after the patch applications were best described by a two-compartment linear model with zero-order absorption (D2) and absorption delay. The relative bioavailability (BA) of donepezil after the patch application compared with oral dosing was described to be affected by the duration of patch application.Conclusion: PK simulations based on the chosen PK models suggested that, overall, donepezil exposure in plasma is similar whether with 10 mg of oral donepezil every 24 h or a 175 mg patch every 72 h, and likewise with 5 mg of oral donepezil every 24 h or an 87.5 mg patch every 72 h.Keywords: clinical trial(s), clinical trial simulation(s), pharmacokinetics, pharmacometrics, analysis